2012
DOI: 10.1105/tpc.112.102046
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Defense against Botrytis cinerea: Chronology and Regulation Deciphered by High-Resolution Temporal Transcriptomic Analysis    

Abstract: Transcriptional reprogramming forms a major part of a plant's response to pathogen infection. Many individual components and pathways operating during plant defense have been identified, but our knowledge of how these different components interact is still rudimentary. We generated a high-resolution time series of gene expression profiles from a single Arabidopsis thaliana leaf during infection by the necrotrophic fungal pathogen Botrytis cinerea. Approximately one-third of the Arabidopsis genome is differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
401
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 325 publications
(438 citation statements)
references
References 158 publications
(205 reference statements)
36
401
1
Order By: Relevance
“…Since woundactivation of VSP2 was strongly diminished in wrky75-25 and maintained after egg extract treatment in 35S: WRKY75, our results are consistent with a positive role of WRKY75 in the control of the JA-regulated genes independently of MYC2. WRKY75 was previously shown to play a role in plant defense against biotrophs and necrotrophs (Encinas- Villarejo et al, 2009;Windram et al, 2012;Chen et al, 2013). Noteworthy, WRKY75 overexpression was accompanied by elevated expression of JA-responsive genes, including PDF1.2, VSP1, and LOX2, and enhanced resistance against the necrotroph Sclerotinia sclerotiorum .…”
Section: Discussionmentioning
confidence: 99%
“…Since woundactivation of VSP2 was strongly diminished in wrky75-25 and maintained after egg extract treatment in 35S: WRKY75, our results are consistent with a positive role of WRKY75 in the control of the JA-regulated genes independently of MYC2. WRKY75 was previously shown to play a role in plant defense against biotrophs and necrotrophs (Encinas- Villarejo et al, 2009;Windram et al, 2012;Chen et al, 2013). Noteworthy, WRKY75 overexpression was accompanied by elevated expression of JA-responsive genes, including PDF1.2, VSP1, and LOX2, and enhanced resistance against the necrotroph Sclerotinia sclerotiorum .…”
Section: Discussionmentioning
confidence: 99%
“…However, the in planta virulence of the pathogen is driven by an interaction of the genetics between both the pathogen and plant. We used digital imaging to measure the spatial characteristics of active lesions at 72 h postinoculation (hpi) in the Arabidopsis thaliana ecotype Col-0 and five of its single-gene mutants that have wellcharacterized deficiencies in pathogen defense, including pad3 (camalexin deficient mutant) (Zhou et al 1999), coi1 (jasmonate receptor) (Xie et al 1998), npr1 (salicylate receptor) (Cao et al 1997), tga3, and anac055 (transcription factors involved with response to B. cinerea) (Windram et al 2012). The use of these mutants allows us to survey how genetic shifts in the plant host will influence the pathogen as a model for shifts in host range.…”
Section: Resultsmentioning
confidence: 99%
“…A previous report demonstrated that the expression of approximately onethird of the A. thaliana transcriptome changes during the first 48 hpi with B. cinerea [32]. Thus, we focused on this window.…”
Section: Effect Of Different Timing In Ases Pre-treatment Against Bmentioning
confidence: 99%